The Role of Good Governance Principles in Improving the Performance of Regional Companies Parking Greater Makassar in City Parking Management - Sulfika, Sulfika; Sakina, Adetria Putri; Ichwan, Rifky Nur (Kybernology : Journal of Government Studies, 2025)
This study examines the role of Good Governance principles in enhancing the performance of Perumda Parkir Makassar Raya in managing urban parking services as mandated by Makassar City Regional Regulation Number 2 of 2021. Using a descriptive qualitative approach, the research explores how transparency, accountability, effectiveness, and operational discipline influence revenue management and service delivery. The findings reveal that limited transparency contributes to inefficiencies, revenue leakage, and declining public trust, while weak accountability mechanisms lead to inconsistent supervision, poor service quality, and reduced organizational discipline. Furthermore, gaps in internal audit systems, unclear SOPs, and weak performance evaluation structures exacerbate governance challenges within the institution. The study concludes that strengthening transparency and accountability simultaneously is essential to improving operational performance, ensuring regulatory compliance, and restoring public trust in parking governance